Closed approximate subgroups: compactness, amenability and approximate lattices - Simon Machado (Forum of Mathematics, Sigma)
We investigate properties of closed approximate subgroups of locally compact groups, with a particular interest for approximate lattices (i.e., those approximate subgroups that are discrete and have finite co-volume).